PEMODELAN DUA DIMENSI (2D) BAWAH PERMUKAAN PULAU ADONARA DENGAN DATA ANOMALI GRAVITASI - K. K. Lesu; Jehunias L. Tanesib; Bernandus Bernandus (Universitas Nusa Cendana, 2023)
Geophysical research has been carried out using the gravity method on Adonara island in east Flores Regency, East Nusa Tenggara. This study aims to determine the subsurface rock geological conditions of the research area using free air gravity anomaly data from GGMplus and ERTM2160. The data is reduced by atmospheric correction, simple bouguer correction, curvature correction to produce a complete bouguer anomaly. After correction, regional anomalies and residual anomalies are separated. Then 2-dimensional (2D) modeling is carried out using forward modeling and inversion modeling with Grav2DC software. The results of the study show that the subsurface geological conditions of Adonara island are dominated rock by andesite, granite, diorite, dolomite, gravel, sandstone, basalt, sekis, metamorphic, shale and lavas.